Analysis of the Area of South Sumatra Industry Growth Centers - Mohammad Abdul Mukhyi (Eduvest - Journal of Universal Studies, 2022)
The formation of an area with certain characteristics that have the potential to grow and develop certain industries As a prime mover for regional development and encourage increased industrial and regional economic growth. The purpose of this study is to analyze the South Sumatra Industrial Growth Center Area in the development of industrial growth areas. The approach taken is a qualitative analysis by looking at portraits in the field. With the formation of this Industrial Growth Center Area, it will become clearer the direction and strategy to be carried out by the level I or level II district and city governments, so that good strategies and planning can be prepared to encourage economic development, especially in the South Sumatra region, so that with the This WPPI can be expected to provide progress and prosperity for the community with a multiplier effect created.